The use of naqli and aqli approaches in affirming islamic creed as reflected in Shaykh Dawud bin 'Abd Allah Al-Fatani's Ward Al-Zawahir - Hasbullah bin Mohamad (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
Shaykh Dawud bin Abd Allah al-Fatani was a great and prolific Muslim scholar who has contributed much to the Malay scholarship in the Malay Archipelago particularly in three major disciplines of the Islamic creed, Islamic jurisprudence, and Sufism. Ward al-Zawahir is among his greatest contributions in Islamic creed, allegedly among the most significant work in theological jawi treatises. This is due to the optimal use of the authoritative arguments on theology of the naqli and aqli propositions in affirming the Islamic creed towards its goal of knowing God (marifat Allah). Dawud al-Fatani argued that the concept of marifat Allah could be achieved through transformational efforts from blind imitation (taqlid) to certainty (yaqin) by employing proper approaches of the naqli and Ñaqli towards its goal, i.e. based on authority. For the sake of authority, he employed the naqli of the revealed sources from the Quranic verses and their interpretation as well as the authorized sources of aÍhadith, be they authentic (sahih) or fair (hasan) alhadith. In contrast, the weak alhadith (daif) is only applicable in the branches of religious practices (furu), the merit of certain deeds (fadail al-amal), and religious advice (al-wa'z). Thus, the application of such alhadith on these would support the authoritative ones. The same goes to his stand toward the aqli that must be derived from the reputable scholars of the Ahl al-Sunnah. In this respect, Dawud al-Fatani's attitude of the authoritative arguments on theology was deductively examined to confirm his hypothesis which would reveal his consistency in dealing with the naqli and aqli. This study eventually indicates that he was consistent with his methodology of the use of the authority of the naqli and aqli in approaching the goal of Islamic creed with some inadequacies of human factor especially in dealing with the Israelite sources (Israiliyyat). The main approach to theology of Dawud al-Fatani's Ward al-Zawahir proved his optimal use of the authoritative arguments of the naqli and aqli towards its goal. This makes his work unique and distinguishable from the classical treatises of other Malay scholars especially in the late of eighteenth to twentieth centuries. Thus, his approaches deserve to be appreciated and serve as the invaluable material in scholarly works inspiring the Ministry of Education, universities, educational institutions, mosques, and students to follow his steps in dealing with the optimal use of the authoritative arguments on theology in affirming the Islamic creed. Therefore, this study is considerably important to pinpoint Dawud al-Fatani's contribution in Islamic creed particularly his Ward al-Zawahir that could serve as the masterpice of theological jawi treatise (which is known as Karya Agung) in the Malay Archipelago